Magma Chamber Detected Beneath an Arc Volcano With Full‐Waveform Inversion of Active‐Source Seismic Data. (1st November 2022) - Chrapkiewicz, K.; Paulatto, M.; Heath, B. A.; Hooft, E. E. E.; Nomikou, P.; Papazachos, C. B.; Schmid, F.; Toomey, D. R.; Warner, M. R.; Morgan, J. V.
Abstract: Arc volcanoes are underlain by complex systems of molten‐rock reservoirs ranging from melt‐poor mush zones to melt‐rich magma chambers. Petrological and satellite data indicate that eruptible magma chambers form in the topmost few kilometres of the crust. However, very few chambers have ever been definitively located, suggesting that most are too short‐lived or too small to be imaged, which has direct implications for hazard assessment and modeling of magma differentiation. Here we use a high‐resolution technology based on inverting full seismic waveforms to image a small, high‐melt‐fraction magma chamber that was not detected with standard seismic tomography. The melt reservoir extends from ∼2 to at least 4 km below sea level (b.s.l.) at Kolumbo—a submarine volcano near Santorini, Greece. The chamber coincides with the termination point of the recent earthquake swarms and may be a missing link between a deeper melt reservoir and the high‐temperature hydrothermal system venting at the crater floor. The chamber poses a serious hazard as it could produce a highly explosive, tsunamigenic eruption in the near future. Our results suggest that similar reservoirs (relatively small but high‐melt‐fraction) may have gone undetected at other active volcanoes, challenging the existing eruption forecasts and reactive‐flow models of magma differentiation. Plain Language Summary: Arc volcanoes, which mark the curved boundaries between converging tectonic plates, host the most explosive events on Earth. The associated hazard depends on how much mobile magma is currently present shallow beneath a volcano. Standard tomographic methods used so far have relatively low resolution and give a blurred picture of only the largest molten‐rock bodies. In particular, they struggle to distinguish between mobile magma and melt spread between tightly packed mineral grains. This study, a first in volcanology, combines a next‐generation tomographic method with extraordinarily dense seafloor recordings of controlled marine sound sources. This state‐of‐the‐art experiment at Kolumbo volcano, offshore of Santorini allowed us to detect a body of mobile magma which has been growing at an average rate of 4 × 10 6 m 3 per year since the last eruption in 1650 CE. This rate is large enough to counteract the effect of cooling and crystallization. Our results show that Kolumbo poses a serious threat and deserves a real‐time monitoring facility. Despite the excellent data coverage, the small magma body was missed by standard tomography. This suggests that applying next‐generation imaging methods to already‐well‐studied volcanoes may lead to similar discoveries. We envision that small‐volume, high‐melt‐fraction reservoirs may be more widespread than previously thought. Key Points: A shallow, very strong negative V p anomaly imaged under the explosive, submarine Kolumbo volcano, Greece, using full‐waveform inversion The high‐fidelity image and petrologic data indicate the anomaly is a small (∼0.6‐km wide, ∼2‐km deep), magma chamber with ∼42% of melt The chamber was missed by travel‐time tomography indicating similar reservoirs may have gone undetected at other volcanoes